1992
DOI: 10.2186/jjps.36.94
|View full text |Cite
|
Sign up to set email alerts
|

The Activity Pattern of the Inferior Head of Lateral Pterygoid Muscle.

Abstract: The purpose of this study was to investigate the functional property of the inferior head of lateral pterygoid muscle (ILP) in jaw movements. Electromyographic recordings (EMG) of bilateral ILP were obtained intraorally by using bipolar fine wire electrodes. In addition, surface electrodes were used on the posterior temporal muscles and the other 4 muscles. Jaw movement data were taken by the 6 degree of freedom digital jaw tracking device (MM-JI). Both EMG and jaw movement were recorded simultaneously in 8 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…MMFP values demonstrated that only the dolichofacial group presented reduced values ( P <0.05), about 2.5 times inferior to those of brachyfacial subjects. The onset of lateral pterygoid activity was delayed in jaw opening as compared to jaw protrusion 27 . During protrusion, both lateral and medial pterygoids are active, which results in decreased transverse arch dimensions, due to their action on the ascending mandibular ramus 27 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…MMFP values demonstrated that only the dolichofacial group presented reduced values ( P <0.05), about 2.5 times inferior to those of brachyfacial subjects. The onset of lateral pterygoid activity was delayed in jaw opening as compared to jaw protrusion 27 . During protrusion, both lateral and medial pterygoids are active, which results in decreased transverse arch dimensions, due to their action on the ascending mandibular ramus 27 .…”
Section: Discussionmentioning
confidence: 89%
“…The onset of lateral pterygoid activity was delayed in jaw opening as compared to jaw protrusion 27 . During protrusion, both lateral and medial pterygoids are active, which results in decreased transverse arch dimensions, due to their action on the ascending mandibular ramus 27 . Therefore, the medial pterygoid activity of dolichofacial subjects could be decreased similarly to the lower values observed for masseter and temporal muscles, while action of lateral pterygoid muscle seems to be shortened.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ueda R in 1992 22 reported that there was no significant difference in lateral pterygoid activity between maximum opening and protrusion which implied that lateral pterygoid is not solely responsible for mandibular distortion during jaw movement.…”
Section: Ijoicrmentioning
confidence: 99%